Polysilicon nanogap lab-on-chip facilitates multiplex analyses with single analyte - Sharma Rao Balakrishnan; U. Hashim; Subash C.B. Gopinath; P. Poopalan; H.R. Ramayya; P. Veeradasan; R. Haarindraprasad; A.R. Ruslinda (Elsevier, 2024)
Biosensors and Bioelectronics Volume 84, 15 October 2016, Pages 44-52